2021
DOI: 10.1016/j.jhep.2020.12.034
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxia inducible factors regulate hepatitis B virus replication by activating the basal core promoter

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
40
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(42 citation statements)
references
References 60 publications
2
40
0
Order By: Relevance
“…In CLD, the survival and proliferation of cells in cirrhotic nodules, which exist in a hypoxic environment, may result from the “stemness” characteristics conferred onto them by HBx ( Figure 1 ). Recently, it has been shown that hypoxia inducible factors bind ccc HBV DNA and activate the basal core promoter, which promotes HBV transcription and replication [ 64 ]. However, HIF may also activate the promoters of HBx (and preS) from the integrated templates encoding these virus products [ 64 ], which may stimulate the appearance of “stemness”, cell survival, and oncogenesis.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In CLD, the survival and proliferation of cells in cirrhotic nodules, which exist in a hypoxic environment, may result from the “stemness” characteristics conferred onto them by HBx ( Figure 1 ). Recently, it has been shown that hypoxia inducible factors bind ccc HBV DNA and activate the basal core promoter, which promotes HBV transcription and replication [ 64 ]. However, HIF may also activate the promoters of HBx (and preS) from the integrated templates encoding these virus products [ 64 ], which may stimulate the appearance of “stemness”, cell survival, and oncogenesis.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, it has been shown that hypoxia inducible factors bind ccc HBV DNA and activate the basal core promoter, which promotes HBV transcription and replication [ 64 ]. However, HIF may also activate the promoters of HBx (and preS) from the integrated templates encoding these virus products [ 64 ], which may stimulate the appearance of “stemness”, cell survival, and oncogenesis. Perhaps this is the reason why there is such strong and consistent staining of HBx in cirrhotic nodules [ 40 , 65 ].…”
Section: Introductionmentioning
confidence: 99%
“…HBV replication is highly restricted to hepatocytes, partly due to hepatocyte-specific expression of the HBV entry receptor, sodium-taurocholate co-transporting polypeptide (NTCP) [ 12 , 13 ] and partly because its transcription relies on hepatocyte-specific transcription factors [ 14 , 15 ]. Cellular entry process is initiated by low-affinity attachment to heparan sulfate proteoglycans (HSPGs), followed by a high-affinity binding of NTCP [ 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…2,3 Thus, one might assume that not much can still be discovered in this small, 3,200 base pair genome. Now, Wing et al 1 show otherwise. They show that cellular hypoxia-inducible factors (HIF-1a, -1b, and -2a) bind as heterodimers to 2 short hypoxia response elements (HREs) upstream of the basal core promoter (BC-Pro) and thereby enhance production of an mRNA encoding both the HBV core protein and the viral DNA polymerase.…”
mentioning
confidence: 98%
“…In this issue of the Journal of Hepatology, a collaboration headed by the laboratory of Jane McKeating describes two new sequence elements in the hepatitis B virus (HBV) DNA genome that mediate transcriptional activation, leading to enhanced production of the viral RNA pregenome, under low oxygen conditions. 1 Transcriptional regulation of the HBV genome has been intensively studied since the late 1970s, and these studies have found numerous transcription factors regulating HBV gene expression. 2,3 Thus, one might assume that not much can still be discovered in this small, 3,200 base pair genome.…”
mentioning
confidence: 99%